The state of bioelectric activity of the myocardium in representatives of swimming - Mykhaliuk, Ye. L.; Hunina, L. M.; Chernozub, A. A. (Zaporozhye Medical Journal, 2018)
The purpose of the work was to study the indices of myocardium bioelectrical activity in representatives (women) of swimming on the 100–400 meters distance, who differ in sports qualification. Materials and methods. The myocardium bioelectrical activity was studied using the diagnostic automated complex "Cardio +". For the purpose of differential diagnosis, athletes with right atrial ectopic rhythm, wandering pacemaker and distortion of the terminal portion of the ventricular complex were subjected to an exercise tolerance test on a bicycle ergometer using the method of submaximal exercise PWC170 test and athletes with CLC syndrome – to echocardiography using an echo-Doppler unit (model Sim 5000 Plus, Italy). Results. Among the representatives of MS-MSIC female swimmers sinus bradycardia is more common and fewer persons with a vertical cardiac axis in comparison with the swimmers of CMS qualification category I and II–III, fewer persons with heart rate 80 beats/min or more and normal voltage in comparison with athletes of qualification category II–III. In the female swimmers of qualification category CMS I a vertical cardiac axis, heart rate 80 beats/min or more, high ECG voltage and T-infantile are less common in comparison with the athletes of the II–III category, but normal ECG voltage and IRBBB are more frequent. Conclusions. In athletes with a right atrial ectopic rhythm and wandering pacemaker the sinus rhythm was restored after an exercise tolerance test using the method of submaximal exercise PWC170 and the ECG normalized in athletes with distortion of the terminal portion of the ventricular complex. In athletes with CLC syndrome, showed by echocardiography, dilation and cardiac hypertrophy have not been revealed, and the presence of IRBBB and EVRS should be considered as features of ECG in this category of athletes.